A preclinical animal study to evaluate the operability and safety of domestic one-way endobronchial valves - Jiao, Yang; Tian, Sen; Liu, Jian; Shen, Xiaping; Wang, Qin; Li, Xiang; Zhang, Wei; Dong, Yuchao; Li, Yonghua; Bai, Chong; Huang, Haidong (Frontiers in Medicine, 2024)
Purpose To evaluate the operability and safety of bronchoscopic domestic one-way endobronchial valves (EBV) on animals. Methods Nine pigs were randomly assigned (2:1) to receive domestic one-way EBV (the experimental group, n = 6) and Zephyr® EBV (the control group, n = 3). Routine blood tests, arterial blood gases, and CT scans of the lungs were performed 1 day pre-procedure in addition to 1 week and 1 month post-procedure to assess changes in blood markers and lung volumes. At 1 month post-procedure, the animals were sacrificed, followed by removal of all valves via bronchoscopy. Pathological examinations of critical organs were subsequently performed. Results A total of 15 valves were placed in the experimental group and 6 valves were placed in the control group, without serious complications. Routine blood tests and arterial blood gas examinations at 1 day pre-procedure, 1 week post-procedure, and 1 month post-procedure did not differ significantly in both groups. No EBV displacement was noted under bronchoscopy, and the valve was smoothly removable by bronchoscope at 1 month post-procedure. At 1 week post-procedure, varying degrees of target lung lobe volume reduction were observed on lung CT in both groups. Lung volume reduction was achieved at 1 month post-procedure in both groups, without significant statistical difference. Although 3 cases in the experimental group and 1 case in the control group developed varying degrees of pneumonia, the inflammatory response did not increase over time during the experimental period. Pathological examination revealed no significant abnormal changes in the critical organs for both groups. Conclusion Our results demonstrate that domestic EBV is safe and reliable for endobronchial application in general-grade laboratory white pigs. The safety of domestic EBV is similar to that of Zephyr® EBV, with good ease of use and operability. This kind of domestic EBV can meet the safety evaluation requirements for animal testing.